Microsatellite markers of the major histocompatibility complex genomic region of domestic camels - Knoll, Ales; Wijacki, Jan; Plasil, Martin; Burger, Pamela A.; Horin, Petr (Frontiers in Genetics, 2022)
We described and characterized 11 polymorphic microsatellite markers suitable for routine testing (three in the MHC class I sub-region, four in MHC class II and four in the MHC class III sub-region) of dromedaries and Bactrian camels. In total of 38 dromedaries and 33 Bactrian camels were genotyped and interspecific differences were observed in the numbers of alleles, in allelic frequencies as well as in observed heterozygosity. These loci may be used as markers to study adaptive genetic diversity of the MHC region in Old World camels.